Mempertahankan Mutu Buah Tomat Segar Dengan Pelapisan Minyak Nabati [Maintaining The Quality Of Fresh Tomatoes With a Coating Of Vegetable Oil] - Nirma Yopita Sari Tarigan; I Made Supartha Utama; Pande K Diah Kencana (Jurnal BETA (Biosistem dan Teknik Pertanian), 2016)
The purpose of this study was to study the effect of emulsion of vegetable oil as coating materials, on the quality and shelf life of different stages of fresh tomatoes during storage at room temperature. The maturity levels of tomato fruits were varied, namely breaker stage, turning stage, pink stage and red stage. The mixed emulsion in water of 0,5%, sesame oil and 0,5%, lemongrass oil was used in this experiment. Additional materials used to make the emulsion were 0,5% oftween 80, 0,5% of oleic acid, and 3% of ethanol. Control fruits without treatments are also prepared for comparison. The experiment was performed using a factorial Completely Randomized Design (CRD) with two factors. The first factor was the use of coating treatment consisted of two levels: coating and without coating. The second factor was the stage of maturity of tomatoes consisted of stage 2, stage 3, stage 4, and stage 5. The results showed that coating the tomato fruits with treatment of the mixed emulsion of sesame oil and lemongrass oil significantly affected the quality and storage life. The coating of tomatoes of the turning stage 3 gave the best results which was able to reduce the pH, color, TPT and total acid.